2018
DOI: 10.1080/09168451.2018.1445518
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic compound, (Z)-5-(3-hydroxy-4-methoxybenzylidene)-2-iminothiazolidin-4-one (MHY773) inhibits mushroom tyrosinase

Abstract: As part of continued efforts for the development of new tyrosinase inhibitors, (Z)-5-(substituted benzylidene)-2-iminothiazolidin-4-one derivatives (1a - 1l) were rationally synthesized and evaluated for their inhibitory potential in vitro. These compounds were designed and synthesized based on the structural attributes of a β-phenyl-α,β-unsaturated carbonyl scaffold template. Among these compounds, (Z)-5-(3-hydroxy-4-methoxybenzylidene)-2-iminothiazolidin-4-one (1e, MHY773) exhibited the greatest tyrosinase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Moreover, 1e significantly inhibited tyrosinase activity, with IC 50 values of 17.44 ± 1.81 μM and 28.72 ± 1.98 μM for both substrate l -tyrosine and l -DOPA, respectively. Recently, we reported the importance of a 3-hydroxy-4-methoxybenzylidene moiety, which contributed to improved activity toward tyrosinase [ 20 ]. Furthermore, compounds 1a , 1b , 1d , and 1f moderately inhibited tyrosinase activity toward l -tyrosine with IC 50 values of 46.16 ± 0.55 μM, 75.72 ± 2.46 μM, 98.78 ± 2.11 μM, and 77.91 ± 8.74 μM, respectively, while 1g and 1h were inactive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, 1e significantly inhibited tyrosinase activity, with IC 50 values of 17.44 ± 1.81 μM and 28.72 ± 1.98 μM for both substrate l -tyrosine and l -DOPA, respectively. Recently, we reported the importance of a 3-hydroxy-4-methoxybenzylidene moiety, which contributed to improved activity toward tyrosinase [ 20 ]. Furthermore, compounds 1a , 1b , 1d , and 1f moderately inhibited tyrosinase activity toward l -tyrosine with IC 50 values of 46.16 ± 0.55 μM, 75.72 ± 2.46 μM, 98.78 ± 2.11 μM, and 77.91 ± 8.74 μM, respectively, while 1g and 1h were inactive.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, biological activities of chalcone-like derivatives are significantly determined based on the position and numbers of functional groups attached to benzene ring. In spite of diverse structural moiety of natural tyrosinase inhibitors and available methodology to reasonably design effective synthetic derivatives, many synthetic tyrosinase inhibitors with novel skeletons have been studied [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Especially, Hwang et al [ 27 ] reported the effects of heterocyclic chalcone derivatives containing heterocycles, such as thiophene or furan ring as an isostere of benzene ring on free radical scavenging activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years several studies have been directed to the development of novel tyrosinase inhibitors inspired by natural scaffolds, which should overcome stability, efficacy, and isolation yield issues. One of the main exploited scaffolds is hydroxycinnamic acid: indeed several hydroxycinnamic acid analogues have been synthesized through the most disparate approaches [123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141], leading in some cases to very potent mushroom tyrosinase inhibitors (Figure 17), such as 2,4-dihydroxycinnamides (IC 50 = 0.0112-0.16 µM) [132,133]. A thiophenyl derivative of 2,4-dihydroxycinnamic acid has also exhibited a very low IC 50 value (0.013 µM) against the monophenolase activity of the enzyme [134].…”
Section: Synthetic Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
“…In the last five years, several natural and synthetic phenolic compounds have been described also as inhibitors of tyrosinase from animal and human sources. Most of these studies used B16 murine melanoma cell lines as a model [52,55,75,85,95,96,99,114,122,123,[127][128][129][132][133][134][135]138,139,151,153,155,163,, although some papers using zebrafish as an in vivo whole animal model have also been published [55,116,206]. As to the human sources, data on inhibition of human recombinant or purified tyrosinase [9,207], human melanoma cells [130,136], normal human melanocytes [208][209][210][211], or human skin models consisting of reconstructed three-dimensional human epidermis [212][213][214][215] have been published (Figure 21).…”
Section: Human and Animal Tyrosinase Phenolic Inhibitorsmentioning
confidence: 99%